EVOLUȚIA ȘCOLII NAȚIONALE DE TAPISERIE DIN CHIȘINĂU - Simac, Ana (Academia de Ştiinţe a Moldovei, 2022)
The national school of tapestry in the Republic of Moldova crystallized in the 60–70s within the increased interest in decorative art. Folk carpet, interior textiles, embroidery and cult fabrics served as a source of inspiration for the establishment of the field of modern textile art. The national school of tapestry took shape in the 70s–80s, thanks to the creation of artists Elena Rotaru, Maria Saca-Răcilă, Carmela Golovinov, Silvia Vrânceanu and others. In those years, the tapestry in the Republic experienced a real flowering process. The diversification of the field in terms of style and technical directions takes place after the 80s of the 20th. The tapestry school tends towards a formal plastic language, often abstract, based on tonal and chromatic relationships. Another generation of artists like Andrei Negură, Ludmila Șevcenko, Ecaterina Ajder, Vasilie Grama, Anaid Culicenco etc. is evolving. The specific feature of decorative arts after the 2000s is the abandonment of figurative compositions in favor of abstract ones. The authors use new textile materials and apply technical innovations. As a result, the alternation of forms, structures, invoices, skill and sensitivity in the choice of chromaticity becomes a priority. Today, the field of tapestry continues to be valued within the higher institutions of artistic education, the field of decorative arts. Young creators are invited to capitalize on traditions in modern formal compositions, synthesizing symbolic essences extracted from the sap of national cultures.
The evolution of the national tapestry school in Chisinau
Keywords: national school of tapestry; textile art; Chișinău istoria; arta tapiseriei; tapiseria